Associations of Fatty Liver Disease and Other Factors Affecting Serum SHBG Concentrations: A Population Based Study on 1657 Subjects - Flechtner-Mors, M.; Schick, A.; Oeztuerk, S.; Haenle, M. M.; Wilhelm, M.; Koenig, W.; Imhof, A.; Boehm, B. O.; Graeter, T.; Mason, R. A.; Kratzer, W.; Akinli, A. S.; null (Hormone and Metabolic Research, 2014)
Sex hormone binding globulin (SHBG) is a glycoprotein expressed predominantly in the hepatocytes. It regulates the transport of sex steroid hormones in the blood stream to their target tissues. The expression of the SHBG gene is subject to multifactorial regulation including hormonal, metabolic, and nutritional aspects. Against this background, we investigated the effect of fatty liver and metabolic syndrome, together with other parameters, on serum SHBG concentrations in a population-based cohort in Germany. This cross-sectional study included 870 women and 787 men (average age 42.3±12.8 years), who underwent ultrasound screening for fatty liver in addition to providing a complete medical history and undergoing physical and laboratory examination. Fatty liver was diagnosed on ultrasound criteria in 159 women (18.3%) and 287 men (36.5%). Fatty liver was shown to exert a significant influence on serum SHBG concentrations in men and in premenopausal women. Men with grade 1 fatty liver had a 1.96-fold increased risk (95%-confidence interval=1.28–3.02; p=0.0022) and postmenopausal women with grade 1 fatty liver a 2.4-fold risk (95%-confidence interval=1.11–5.27; p=0.0267) for low SHBG concentrations. Among metabolic parameters, HDL-C represented as affecting factor in men (p=0.0058) and premenopausal women (p=0.0002), while cholesterol only showed an association in premenopausal women (p=0.0439) and triglyceride in postmenopausal women (p=0.0436). No association of concentrations of SHBG and metabolic syndrome was observed. Age, BMI and waist-to-hip ratio also influence the SHBG concentration. Based on these findings, we conclude that fat accumulation in the liver influences SHBG concentrations in men and premenopausal women.
Keywords: NAFLD; ultrasonography; metabolic syndrome; cross-sectional-study